Antioxidant Activity of Endophytic Bacteria Derived from Hoya multiflora Blume Plant and Their Cellular Activities on Schizosaccharomyces pombe - Nabila Tsoerayya Gustia Pudjas; Nisa Rachmania Mubarik; Rika Indri Astuti; Lisdar I Sudirman (Bogor Agricultural University, Indonesia, 2022)
Endophytic bacteria isolated from plant tissues can produce the same secondary metabolites as their host plants. One of the metabolites that the bacteria can produce is antioxidants. This research aimed to analyze and measure the antioxidant activities of two endophytic bacteria, i.e. Bacillus siamensis HMB1 and Bacillus aryabhattai HMD4 cultures, derived from Hoya multiflora Blume plant, a tropical epiphytic plant species that grows in Indonesia, and to identify their cellular effects on Schizosaccharomyces pombe. The active compounds went through extraction process, and the antioxidant activities were measured, the extracts went under phytochemical analysis, and their phenol and flavonoid contents were measured. In vitro analysis was carried out using S. pombe. The results of this research indicated that both cultures had antioxidant activities, where HMB1 showed the highest IC50 value (51.18 mg/ml) among all. In vitro analysis indicated that HMD4 bacterial crude extract in 250 ppm concentration showed the highest resistance effect and significantly enhanced S. pombe growth. In addition, the results of the LC-MS analysis suggested that a total of 14 compounds potentially had antioxidant activity.